A review of research on Project STAR and path ahead. Issue 2 (2nd April 2016) - Sohn, Kitae
Abstract : Understanding the effects of class size reduction (CSR) has been an enduring issue in education. For the past 3 decades, Project STAR has stimulated research and policy discussions regarding the effects of CSR on a variety of outcomes. Schanzenbach (2007) reviewed STAR studies and concluded that small classes improved student academic outcomes. Since her review, however, some research has challenged this conclusion. This paper reviews these recent challenges, comparing past and recent studies. This review is considered together with studies on large-scale CSR policies in the US and CSR studies outside the US. We conclude by suggesting a direction for future research.